Multiple modes of shoreline change along the Alaskan Beaufort Sea observed using ICESat-2 altimetry and satellite imagery - M. B. Bryant; A. A. Borsa; E. J. Anderson; E. J. Anderson; C. C. Masteller; R. J. Michaelides; M. R. Siegfried; M. R. Siegfried; A. P. Young (The Cryosphere)
Arctic shorelines are retreating rapidly due to declining sea ice cover, increasing temperatures, and increasing storm activity. Shoreline morphology may influence local retreat rates, but quantifying this relationship requires repeat estimates of shoreline positions and morphologic properties. Here we use a novel combination of shoreline boundaries from multispectral imagery from Planet and topographic profiles from the Ice, Cloud and land Elevation Satellite 2 (ICESat-2) altimeter to compare year-to-year changes in shoreline position and morphology across different shoreline types, focusing on an 8 km stretch of the Alaskan Beaufort Sea coast during the 2019–2021 open-water seasons. We consider temporal and spatial variability in shoreline change in the context of environmental forcings from ERA5 and morphologic classifications from the ShoreZone database. We find a mean spatially averaged shoreline change rate of −16.5 m a−1 over 3 years, with local estimates ranging from −66.7 to +18.6 m in a single year. We posit that annual and kilometer-scale variability in shoreline change can be explained by the response of different geomorphic units to time-varying wave and ocean conditions. Ice-rich coastal bluffs and inundated tundra exhibited high retreat that is likely driven by high temperatures and wave exposure, while the stretch of shoreline with vegetated peat in front of a large breached thermokarst lake remained relatively stable. Our topographic profiles from ICESat-2 sample three distinct shoreline types (a bluff, a small drained lake basin, and a dune in front of a large drained lake basin) that exhibit different patterns of shoreline change (in terms of both position and morphology) over the 3-year study period. Analysis of altimetry-derived morphologic parameters such as elevation and slope and small-scale features such as toppled blocks and surface ponding provide insight into specific erosion and accretion processes that drive shoreline change. We conclude that repeat altimetry measurements from ICESat-2 and multispectral imagery provide complementary observations that illustrate how both the position and the topography of the shoreline are changing in response to a changing Arctic.